How scientific concept develops: Languaging in collaborative writing tasks. (April 2022) - Li, Chen; Yang, Luxin
Abstract: This qualitative case study explored the extent to which learners' L2 writing concepts changed across different collaborative writing tasks, and how languaging helped learners make meaning between scientific and spontaneous concepts. Four first-year MA students from a Chinese university formed a study group and engaged in collaborative writing tasks as required by an Academic English Reading and Writing course. Multiple sources of data were collected, including audio-taped group discussions, group writings, individual reflections, and course-related documents. Data analysis demonstrated the microgenetic evolving trajectories of the rhetorical modes of "maintaining the flow of information". The participants progressed from spontaneous knowledge of those concepts to a scientific system through languaging about a text containing these conceptual features. Learners' conscious usage of scientific terms, constant revisiting to their prior knowledge, and critical reading of the academic text highlight the mediating role of languaging in empowering the dynamic interaction between scientific reasoning and spontaneous thinking. This study suggests that the integration of stylistic analysis tasks, peer collaboration, and rhetorical concepts may facilitate the transformation of students' thinking patterns as well as the development of their L2 academic literacies. Highlights: Languaging mediates the dynamics between learners' spontaneous thinking and scientific reasoning. Languaging empowers learners' conceptual development. The integration of stylistic analysis, peer work, and genric concepts may facilitate L2 academic literacy development. Learners' scientific concepts develop across the several collaborative writing tasks executed repeatedly.